Comparison of an athlete training for 400m hurdles - Case report - Ledecká, D.; Rošková, M. (Slovak Journal of Sport Science, 2021)
Introduction: The 400 m hurdles run is considered to be a demanding discipline from both a physical and psychological point of view, as it involves coordination skills within an intense duration of activity. To determine the range of general and special training indicators and what impact they had on the performance of the monitored racer. Objectives: The case study aims to analyze and compare two annual training cycles of a 400 m hurdles runner based on general and special training indicators and their impact on sports performance. Results: In the second season, the racer ran more acceleration and maximum speed, which contributed to the improvement of personal records. She completed a volume of speed endurance of 18 km, which was an increase of 6 km, and she completed a special endurance of 32 km, where there was an increase of 8 km compared to the first season. The accumulated volume of kilometers of tempo endurance is approximately the same in both monitored years. In the second season, it is possible to see an increase in the volume of general endurance by 40 km. It is also possible to record an increase in the volume of kilometers in the second season by 4 km. During the first season, the racer ran 780 kilometers and in the next season, there was an increase of 52 kilometers. Conclusion: Based on the findings, the author concluded that the 400 m hurdles run has been largely influenced by the number of units of training which influenced also the overall range of special training indicators and by the improvement of the hurdles crossing technique - maximum and acceleration speed, general, tempo, special and speed endurance.